Occurrence of giardia spp. in dog feces on the Laranjal beach, Pelotas-RS and comparative study between techniques - Ferraz, Alexsander; Ança Evaristo Mendes Cardoso, Tainá; Santos Pires, Bruna; Ávila Antunes, Tatiana; Moscarelli Pinto, Diego; Quintana Nizoli, Leandro (Pubvet, 2018)
Giardiosis is an important zoonotic disease caused by protozoa, easily disseminated by ingestion of cysts in water and food. For the identification of these parasitological agents, the coproparasitological laboratory techniques are prioritized, being some of them the method of Faust and the technique of Hoffman, Pons and Janner (HPJ). The objective of this study was to evaluate samples of feces from dogs, collected on the shore of the Laranjal beach, county of Pelotas, Rio Grande do Sul, Brazil, and to compare these two diagnostic techniques, used in laboratory routine . Of the 41 samples analyzed by both techniques, nine were positive by the method of Faust and seven by HPJ, representing 22% and 17% respectively. Because it is a public place and giardiosis has zoonotic potential, it is necessary to adopt sanitary measures aimed at reducing the contamination of these places and consequently the exposure to this protozoan.
Keywords: comparison of techniques; diagnostic; giardiasis; protozoan; zoonosis